Ethyl-substituted erythromycin derivatives produced by directed metabolic engineering - Stassi, D. L. (The National Academy of Sciences, 1998)
A previously unknown chemical structure, 6-desmethyl-6-ethylerythromycin A (6-ethylErA), was produced through directed genetic manipulation of the erythromycin (Er)-producing organism Saccharopolyspora erythraea. In an attempt to replace the methyl side chain at the C-6 position of the Er polyketide backbone with an ethyl moiety, the methylmalonate-specific acyltransferase (AT) domain of the Er polyketide synthase was replaced with an ethylmalonate-specific AT domain from the polyketide synthase involved in the synthesis of the 16-member macrolide niddamycin. The genetically altered strain was found to produce ErA, however, and not the ethyl-substituted derivative. When the strain was provided with precursors of ethylmalonate, a small quantity of a macrolide with the mass of 6-ethylErA was produced in addition to ErA. Because substrate for the heterologous AT seemed to be limiting, crotonyl-CoA reductase, a primary metabolic enzyme involved in butyryl-CoA production in streptomycetes, was expressed in the strain. The primary macrolide produced by the reengineered strain was 6-ethylErA.